Educational games as a strategy for teaching about inorganic salts: a card game of ions (Research, Society and Development, 2018)
This work describes a classroom experience using a pedagogical game set by the authors with the goal of assist the student in education learning, nomenclature and chemical reactions of inorganic salts, as well as their importance in health. This experience was developed in the chemistry classes of a class of the 1st grade of the High School of a private school in the city of São Paulo. During the application of the game the students could question in, systematize and build up their knowledge about inorganic salts and develop the ability to work in teams. The result of this experience evidences that the game provided moments of fun, narrowing of social relations in the school environment, overcoming difficulties, furthermore the construction of knowledge of structure, nomenclature, reactions and the function of inorganic salts.